Goodbye, my Havana : the life and times of a gringa in revolutionary Cuba - Veltfort, Anna (Redwood Press, 2019)
"A compelling graphic novel-memoir of the author's decade or so experiences as a gringa teenager brought to Cuba by parents supportive of the revolution and ultimately forced to flee during the political crackdowns that consolidated Castro's power and that, for lesbians and homosexuals, were harrowing in a particular kind of way"--